DEVELOPMENT OF THE LITERA DISA WEBSITE (DISABILITY LITERACY) AS A MEANS OF CHARACTERING FOR STUDENTS WITH SPECIAL NEEDS (DEAF) - Ahmad Fadly (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2022)
This development research is motivated by the obstacles faced by deaf students in accessing literary references. The availability of references is important in the continuity of learning so that the competence of literary subjects can be achieved. This study also aims to support the Learning Innovation Program and Assistive Technology (Assistive Technology) for Students with Special Needs designed by the Ministry of Education and Culture of the Republic of Indonesia. Through the development procedure, this service activity produces a product in the form of the Litera Disa Website. A website that contains teaching materials that are deaf-friendly, contains literary materials and examples of their application. Both content and product specifications have gone through the stages of expert assessment and testing to users. With the Litera Disa Website that can be accessed and transmitted via mobile devices, it is hoped that deaf students who study literature can be helped in understanding literary subjects.